2008
DOI: 10.1016/j.pain.2008.02.032
|View full text |Cite
|
Sign up to set email alerts
|

NK-1 receptors in the rostral ventromedial medulla contribute to hyperalgesia produced by intraplantar injection of capsaicin

Abstract: The rostral ventromedial medulla (RVM) is an area of the brainstem involved in the descending modulation of nociception at the level of the spinal cord. Although the RVM is involved in the inhibition or facilitation of nociception, the underlying mechanisms are not understood. Here we examined the role of the neuropeptide substance P and neurokinin-1 (NK-1) receptors located in the RVM on withdrawal responses evoked by mechanical and heat stimuli applied to the rat hindpaw under normal conditions and during hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
51
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 67 publications
13
51
1
Order By: Relevance
“…dose of L-733,060 and GR 159897 in rats, however a wide dose range (from picomolar to micromolar: Pacharinsak et al, 2008;Rittner et al, 2007;Walsh et al, 1995) was used in the case of other routes of administration. The applied doses in the present study (1 nmol for L-733,060 and 0.5 nmol for GR 159897) were based partly on our preliminary results, partly on the estimated affinity of these ligands for the NK1 and NK2 receptors, respectively, derived from in vitro studies (Beresford et al, 1995;Seabrook et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…dose of L-733,060 and GR 159897 in rats, however a wide dose range (from picomolar to micromolar: Pacharinsak et al, 2008;Rittner et al, 2007;Walsh et al, 1995) was used in the case of other routes of administration. The applied doses in the present study (1 nmol for L-733,060 and 0.5 nmol for GR 159897) were based partly on our preliminary results, partly on the estimated affinity of these ligands for the NK1 and NK2 receptors, respectively, derived from in vitro studies (Beresford et al, 1995;Seabrook et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Their responsiveness to excitatory glutamatergic inputs is not altered after inflammatory injury. In the absence of inflammatory injury, microinjection of NK1 receptor antagonists in the RVM does not alter either thermal or mechanical thresholds to noxious stimulation (Pacharinsak et al 2008) (M. Hamity, S. White, and D. L. Hammond, unpublished observations). Thus, it is unlikely that this class of neuron is involved in the modulation of persistent inflammatory nociception in the spinal cord dorsal horn (Kincaid et al 2006;Xu et al 2007; but see Miki et al 2002).…”
Section: Functional Properties Of Rvm Neuronsmentioning
confidence: 96%
“…However, the responsiveness of these neurons to excitatory glutamatergic inputs is dramatically increased after inflammatory injury, an effect that is prevented by a low concentration of L-703,606. Microinjection of NK1 receptor antagonists in the RVM alleviates thermal hyperalgesia and mechanical allodynia produced by intradermal capsaicin (Pacharinsak et al 2008) or intraplantar injection of CFA in the hindpaw (Hamity et al 2008). Thus a subset of type 2 nonserotonergic neurons are likely to function as pain facilitatory neurons.…”
Section: Functional Properties Of Rvm Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Which substances mediate this process? While it is not determined, there are many options based on the following evidence: (1) glutamate; intra-RVM administration of a NMDA receptor antagonist (MK-801) reduces neuropathic pain; the activation of glial cells in the spinal cord during a neuropathic process is also blocked by intrathecal MK-801 (Wei and Pertovaara, 1999;Watkins and Maier, 2002); (2) cholecystokinin (CCK); CCK B receptor antagonist into RVM also reduced neuropathic pain (Kovelowski et al, 2000); (3) ATP; several ATP purinergic receptors are detected in RVM, and direct application of ATP in this area modulates the activity of a subclass of neurons (Selden et al, 2007); (4) substance P (SP); NK-1 receptor located in RVM contributes to hyperalgesia induced by capsaicin (Pacharinsak et al, 2008); SP is also implicated in peripheral nerve lesion-induced glial cell activation in the spinal cord (Watkins and Maier, 2002); and (5) fractalkine; CX3CR1 receptor is constitutively expressed in RVM, and fractalkine is a well known activator of microglia in the spinal cord during neuropathies (Watkins and Maier, 2002;Zhang et al, 2008). Wei et al (2008) found that activation of microglia and astrocytes had different time courses.…”
mentioning
confidence: 99%